Moe Levine on advocacy - Levine, Moe (Portland, OR Trial Guides, 2009)
From the Foreword: "Over 30 years ago, as a young law student, I was front row at a trial lawyer seminar that announced the next speaker, Moe Levine from New York. At the time I had never heard of Moe. However what I witnessed thereafter was truly a career changing epiphany. The lights were dim and onto the raised platform came an elderly man, obviously in poor health with little vision. Moe stood in the spotlight and began to deliver the closing argument in an injury case. For 30 minutes I sat spellbound engrossed in the passion of this imaginary case, real tears fell down my cheeks and those surrounding me, an experience I will never forget." Don Keenan, Child Advocate, and Inner Circle member
Forewords by Don C. Keenan and Russell Corker; afterword by Louise E. Schwartz.
Keywords: Trial practice--United States